Education for the Sustainable Global Citizen: What Can We Learn from Stoic Philosophy and Freirean Environmental Pedagogies? - Kai Whiting; Leonidas Konstantakos; Greg Misiaszek; Edward Simpson; Luis Gabriel Carmona (MDPI AG, 2018)
In support of sustainable development, the United Nations (UN) launched its Global Education First Initiative (GEFI) with the aims of accelerating progress towards universal access to education, good quality learning and the fostering of global citizenship. This paper explores how and to what extent Stoic virtue ethics and critical Freirean ecopedagogies can advance the UN’s vision for progressive educational systems with transformative societal effects. We propose an integrated solution that provides ecopedagogical concepts a more robust philosophical foundation whilst also offering Stoicism additional tools to tackle 21st-century problems, such as climate change and environmental degradation. The result of the paper is the preliminary theoretical underpinnings of an educational framework that encompasses planetary-level concerns and offers a fuller expression of the terms “sustainable development„ and “global citizen„.